Characterization of Glycoprotein 5-Specific Response in Pigs Vaccinated with Modified Live Porcine Reproductive and Respiratory Syndrome Virus Vaccine Derived from Two Different Lineages - Jing Huang; Venkatramana D. Krishna; Igor A. D. Paploski; Kimberly VanderWaal; Declan C. Schroeder; Maxim C.-J. Cheeran (Vaccines)
Background/Objectives: Porcine reproductive and respiratory syndrome virus (PRRSV) is classified into various lineages based on the phylogenetic variation of orf5, which encodes a major surface glycoprotein GP5 containing both neutralizing and non-neutralizing linear epitopes. Several positively selected sites have been identified on the GP5 ectodomain, indicating host immune pressure on these sites. This present study aimed to investigate the kinetics of antibody responses to GP5 and to map the epitope-specific response to the GP5 ectodomain from different PRRSV lineages after vaccination with commercially available modified live virus (MLV) vaccines. Methods: Post-weaning pigs were vaccinated with MLV vaccines derived from either lineage 1D (Prevacent PRRS®) or lineage 5 (Ingelvac PRRS®). Animals were challenged with a heterologous (lineage 1A) strain at 64 days post-vaccination (dpv). Blood samples were collected at various times post-vaccination and challenge. Kinetics of antibody response to different PRRSV antigens were monitored and virus neutralization against archetypal and contemporary strains belonging to lineage 5 and 1A were evaluated. In addition, antibody responses to peptides derived from the GP5 ectodomain of different viral lineages were assessed. Results: Our results showed that the GP5-specific antibody response observed between 18 and 35 dpv was delayed compared to responses to the viral nucleocapsid protein. The polyclonal antibody response in both vaccinated groups showed similar levels of binding to variant GP5 peptides from different sub-lineages. Notably, in both vaccinated groups, the antibody directed to a peptide representing the GP5 ectodomain of a lineage 1C strain (variant 1C.5) displayed a rise in titer at 64 dpv, which was further increased by the challenge with the lineage 1A strain. Less than 50% of animals developed heterologous neutralizing antibodies post-vaccination with both MLV vaccines. However, higher neutralization titers were observed in all vaccinated animal post-challenge. Conclusions: Together, these data provide insights into the antibody responses to the GP5 ectodomain in MLV-vaccinated swine herds.